A 37-Year-Old Schizophrenic Woman With Abdominal Pain - Yiqun Liao; Yue Ma; Fei Chao; Yong Wang; Ziming Zhao; Jun Ren (Clinical Medicine Insights: Case Reports, 2023)
Introduction: Internal fistula across the posterior wall of stomach and the transverse colon caused by foreign bodies in the alimentary tract presents an extremely rare medical entity. Presentation of case: We report an aschizophrenia female patient with onset of internal fistula across the posterior wall of stomach and the transverse colon triggered by swallowed magnetic metal beads. The patient was admitted to the emergency room of Northern Jiangsu People’s Hospital because of acute right lower abdominal pain. Emergency routine abdominal CT scan revealed acute appendicitis and a set of foreign body in digestive tract. Discussion: The foreign body in the stomach was removed by open surgery after tentative Endoscopic foreign body removal and laparoscopic appendectomy and exploration. In the process of exploring the gastric wall, it was found that one of magnet beads was embedded in the posterior wall of stomach and adhered to part of the transverse colon. After separation, it was found that an internal fistula was formed across the posterior wall of stomach and the transverse colon. As the patient ate only a small amount of food within 2 days, and the intestines were in good condition, we performed partial transverse colectomy, end-to-side anastomosis and gastric wall repair. Conclusion: This case shows that for long-term foreign bodies in the digestive tract, we should be beware of the onset of gastrointestinal perforation. Moreover, perforation caused by the force acting on a blunt foreign body often results in atypical imaging findings, and the diagnosis of perforation cannot be clearly determined by imaging findings such as the presence of free gas downstream of the diaphragm. This poses new challenges for clear diagnosis and treatment.